Strategi Dakwah Pondok Pesantren Hidayatullah dalam Mencetak Generasi Santri yang Berakhlakul Karimah - Aan Setiawan (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Islamic da'wah institution, which focuses on education, is currently experiencing a decline. The change proves this in the social order, which is very far from normative values. In line with the technological development that hits almost most people in various parts of the world, it has brought societal changes. The most fundamental change is in the behavior in society, which now requires da'wah interpreters to discover the most effective method and follow the level of community behavior development. A change for a better life is the hope of every human, and it can be realized if there is a concrete, structural and maximal effort. The boarding school of Hidayatullah is an agent of change based on cultivating and building human characters. In this context, the researcher focuses on the effort of this school in creating a student with noble characters and behaviors and some factors which influence it in implementing the da'wah strategies by using the qualitative method approach, and the data collections are gathered by, and documentation. This research aims to explore the strategies teachers implement to build noble characters of santri. The findings show their strategies are standard rules implementation, an exemplification, and extracurricular activities.